2010
DOI: 10.1111/j.1447-0756.2009.01143.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the ERα and CYP1B1 genes in endometrial cancer in a Polish subpopulation

Abstract: The CYP1B1 and ERalpha genes may play a role in endometrial cancer and the Arg48Gly (142C > G) -CYP1B1 and 975C > G-ERalpha polymorphisms may be considered as independent, early diagnostic markers in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…CYP1B1 upregulation is thought to instigate cellular damage by catalyzing the hydroxylation of estrogens, and it can disrupt cellular proliferation through interference with cell cycle regulation [29,45]. Polymorphisms of the CYP1B1 codons result in hyperactivation, and have been shown to impart increased incidence in endometrial cancer, [45,46] though the findings have been conflicting [42,46]. In a separate pathway, estrogens bind to the estrogen receptor ligand binding domain, resulting in stimulation of cell proliferation in these target tissues [46].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…CYP1B1 upregulation is thought to instigate cellular damage by catalyzing the hydroxylation of estrogens, and it can disrupt cellular proliferation through interference with cell cycle regulation [29,45]. Polymorphisms of the CYP1B1 codons result in hyperactivation, and have been shown to impart increased incidence in endometrial cancer, [45,46] though the findings have been conflicting [42,46]. In a separate pathway, estrogens bind to the estrogen receptor ligand binding domain, resulting in stimulation of cell proliferation in these target tissues [46].…”
Section: Discussionmentioning
confidence: 98%
“…Polymorphisms of the CYP1B1 codons result in hyperactivation, and have been shown to impart increased incidence in endometrial cancer, [45,46] though the findings have been conflicting [42,46]. In a separate pathway, estrogens bind to the estrogen receptor ligand binding domain, resulting in stimulation of cell proliferation in these target tissues [46]. Polymorphisms of estrogen receptor alpha likewise have been implicated in conferring increased risk of endometrial cancers in a recent pilot study by Sliwinski, et al [46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CYP1B1 is over expressed in several human tumors in comparison with normal tissues 58,60,61 . CYP1B1 in modulating the incidence of several types of cancers 62,63 . CYP1B1 with the increased risk of ovarian, endometrial, renal, and prostate cancers as well as smoking related lung cancer has been reported in the Caucasian and the Japanese populations 64 .…”
Section: Cyp1a1mentioning
confidence: 99%